Penerapan model pembelajaran inkuiri sebagai upaya untuk meningkatkan prestasi belajar matematika - I Gede Budiarsa (Indonesian Journal of Educational Development, 2021)
This research was conducted at SMK Negeri 3 Tabanan Class XI DPIB Semester II where the ability of students for the level of student achievement in Mathematics learning is still very low. The purpose of writing this classroom action research is to find out whether the application of the Inquiry Learning Model can improve the achievement of mathematics learning outcomes. The subjects of this study were students of class XI DPIB semester II of SMK Negeri 3 Tabanan in the 2018/2019 academic year, while the object of research was the achievement of student mathematics learning outcomes. The data collection method in this research is the mathematics learning achievement test of the students. The data analysis method is descriptive. The indicators of success or the criteria for success in this study were determined that the average value was minimum at 70. The results obtained from this study are the application of the Inquiry Learning Model can improve the mathematics learning achievement of class XI DPIB semester II students as evidenced by the results obtained previously or the initial class average value was 62.50 and in cycle I increased to 68.26 with an increase in learning achievement of 5.76 (9.22%) and in the second cycle it increased again with a class average of 72.32 with an increase in achievement of 9.82 (15.71%). Thus the results that the application of the Inquiry Learning Model can improve the mathematics learning achievement of Class XI DPIB Semester II students of SMK Negeri 3 Tabanan in the 2018/2019 academic year. Penelitian ini dilaksanakan di SMK Negeri 3 Tabanan Kelas XI DPIB Semester II yang kemampuan siswanya untuk tingkat prestasi belajar Matematika siswa masih sangat rendah. Tujuan penulisan penelitian tindakan kelas ini adalah untuk mengetahui apakah dengan penerapan model pembelajaran inkuiri dapat meningkatkan prestasi hasil belajar Matematika. Subjek penelitian ini adalah siswa kelas XI DPIB semester II SMK Negeri 3 Tabanan Tahun Pelajaran 2018/2019, sedangkan objek penelitiannya adalah prestasi hasil belajar matematika siswa. Metode pengumpulan data dalam penelitian ini adalah tes prestasi belajar Matematika siswa. Metode analisis datanya adalah deskriptif. Indikator keberhasilan atau kriteria keberhasilan dalam penelitian ini ditetapkan rata-rata nilainya minimal 70. Hasil yang diperoleh dari penelitian ini adalah dengan Penerapan Model Pembelajaran Inkuiri dapat meningkatkan prestasi belajar Matematika siswa kelas XI DPIB semester II yang dibuktikan dari hasil yang diperoleh sebelumnya atau nilai awal rata-rata kelasnya adalah 62,50 dan pada siklus I meningkat menjadi 68,26 dengan peningkatan prestasi belajar sebesar 5,76 (9,22%) dan pada siklus II meningkat kembali dengan rata-rata kelas 72,32 dengan peningkatan prestasi sebesar 9,82 (15,71%). Dengan demikian penerapan model pembelajaran inkuiri dapat meningkatkan prestasi belajar Matematika siswa Kelas XI DPIB Semester II SMK Negeri 3 Tabanan Tahun Pelajaran 2018/2019.